Islamic geometric patterns - Broug, Eric (London Thames & Hudson Ltd, 2019)
"The marvels of Islamic patterns--the most recognizable visual expression of Islamic art and architecture--are not just a beautiful accident. The ancient practitioners of this craft used traditional methods of measurement to create dazzling geometric compositions, often based on the repetition of a single pattern. The results are magnificent in their beauty and awe-inspiring in their execution. Now, with the aid of this book, everyone can learn how to master this ancient art and create their own intricate patterns or re-create classic examples. All that is needed is a pencil, a ruler, a compass, and a steady hand. Technical tips demonstrate the geometric basics such as how to create designs from one of the foundational "family" shapes: a square, hexagon, or pentagon. This is followed by step-by-step instructions for reproducing some of the best examples of geometric patterns." -- From Amazon.com
"Revised and expanded edition with new patterns from across the Islamic world." -- Front cover
"With 370 illustrations."
First edition translated from the Dutch.
Originally published: 2008.
Includes bibliographical references (page 134).
Keywords: Islamic decoration and ornament; Decoration and ornament, Architectural -- Islamic countries; Repetitive patterns (Decorative arts) -- Islamic countries